Solid-state anaerobic digestion of rice straw pretreated with swine manure digested effluent. (10th May 2022) - Zheng, Haomin; Tang, Fangyi; Lin, Yunqin; Xu, Zhiyong; Xie, Zenghua; Tian, Jun
Abstract: Solid-state anaerobic digestion (SSAD) is a key technology for utilization of agricultural waste due to higher volumetric methane productivity, having a high load of organics, and nearly no effluent produced. The swine manure digested effluent (SMDE) containing high concentrations of ammonia nitrogen (1000, 1500, and 2000 mg L −1, respectively) were innovatively used to pretreat rice straw replacing alkaline chemicals at 30 °C for 2d, 4d, 6d, 8d, and downstream processed in SSAD loaded with solid digestate of swine manure (SDSM). After pretreatment, the surface structure of rice straw was obviously destroyed, and the removal rates of lignin, cellulose and hemicellulose were 1.3–20.4%, 1.3–26.3% and 13.9–28.4%, respectively. The concentrations of ammonia nitrogen in the pretreatment system were reduced by 16.75–75.47%. In the subsequent SSAD process, the accumulative methane yields in the digester loaded with pretreated rice straw increased by 93.25–261.08%, and the technical digestion time to achieve 80% of the maximum cumulative methane yield (T80) occurred 10–14 days earlier. The highest daily methane yield and accumulative methane yield of 7.37 mL/(g·VSadded ·d) and 105.27 mL/(g·VSadded ), respectively, were noted in the digester loaded with 2000 mg/L ammonia pretreated rice straw. Overall, SMDE pretreatment could significantly improve the biodegradability and anaerobic digestibility of rice straw, and improve the production efficiency of SSAD. The novel integrated approach to reutilization of SMDE, rice straw and SDSM not only reduced the environmental pollution, but also stimulated the sustainable development of swine farms, and promoted the carbon neutrality and economic development via effective bioenergy production as well. A large-scale trial and wide application of this approach could be expected in future. Graphical abstract: Image 1 Highlights: Digestate effluent pretreatment effectively improved the biodegradability of rice straw. Solid-state anaerobic digestion of pretreated rice straw and solid digestate was feasible. Accumulative methane yields of pretreated rice straw increased by 93.25–261.08%. Best performances were obtained from rice straw pretreated with 2000 mg/L ammonia for 4 days. Utilization of liquid and solid digestate promoted the sustainable development of swine farms.